2019
DOI: 10.1073/pnas.1903829116
|View full text |Cite
|
Sign up to set email alerts
|

Shearwaters know the direction and distance home but fail to encode intervening obstacles after free-ranging foraging trips

Abstract: SignificanceProcellariiform seabirds homing from distant foraging locations present a natural situation in which the homing route can become obstructed by islands or peninsulas because birds will not travel long distances over land. By measuring initial orientation from Global Positioning System (GPS) tracks during homing, we found that the Manx shearwater fails to encode such obstacles while homing, implying a navigation system that encodes the direction of home rather than a learned route. Nonetheless, shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The tracks of all displaced birds are shown in figure 2 a,b .
Figure 2The tracks of released birds that go the short route ( a ) and long route ( b ) around the island of Ireland are shown; ( c ) shows the homing trips of free-ranging shearwaters (17 trips from 16 birds) hitting the coast of Ireland and proceeding via the short route on their homing journeys [2,3].
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tracks of all displaced birds are shown in figure 2 a,b .
Figure 2The tracks of released birds that go the short route ( a ) and long route ( b ) around the island of Ireland are shown; ( c ) shows the homing trips of free-ranging shearwaters (17 trips from 16 birds) hitting the coast of Ireland and proceeding via the short route on their homing journeys [2,3].
…”
Section: Resultsmentioning
confidence: 99%
“…Manx shearwaters, Puffinus puffinus , and other procellariform seabirds do not routinely travel large distances over land [1]. In this system, topographic features, such as islands and peninsulas, create natural barriers in the environment that present contrasts between the shortest flyable route (over only water) and the direction home notwithstanding the obstacle (henceforth beeline, [2,3]). If homing is guided by true navigation (TN), navigation from beyond sensory contact with a goal and without the requirement for experience from that specific location using exocentric sensory cues [4,5], then this might be indicated when birds are unable to use knowledge of available routes that are more efficient than the beeline home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these rafts form for only a few hours and consist of many thousands of shearwaters, and we did not find evidence for individuals rafting in consistent locations (Supporting information), making this hypothesis unlikely. Furthermore, it has been previously observed that shearwaters returning from long, self‐maintenance trips tend to return to the nest immediately following their commute, rather than spending any time rafting (Padget et al 2019). Consequently, they are likely to return to the nest immediately following their foraging trip, eliminating the possibility of meeting their partner in the waters around the colony.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 5 we provide a schematic proposing possible spatial scales at which key sensory modalities (vision, olfaction, magnetoreception, hearing) and proposed infrasound scenarios may be used by seabirds to obtain spatial information. Some seabird species home in a straight line (Catard and Weimerskirch, 1999, movement data drawn as Figure 2 in Benhamou et al, 2003;Padget et al, 2019), and because infrasound is not influenced by surface-level wind fields to the same degree as odour plumes, birds could use an infrasound beacon over large spatial scales, provided that they are able to identify the direction of the sound source and where this source is located close to the goal (Figure 4A). However, there are several limitations with a directional hearing mechanism along these lines, given seabird flight speeds and interaural time differences (see section "Can Infrasound be Detected by Birds?").…”
Section: How Might Seabirds Use Infrasound For Navigation?mentioning
confidence: 99%